Fatores motivacionais relacionados à permanência do discente na Universidade: um estudo com graduandos da Universidade Federal do Ceará (UFC) - Rodrigues, Rafael do Nascimento (2024)
Not unlike other spheres of life, motivation plays an important role in the academic context. Therefore, research related to understanding the critical motivational factors associated with the student's stay at university may contribute to efficiency in the teaching and learning process. In this sense, the present quantitative work, with a descriptive approach, has the general objective of investigating the motivational factors that affect the retention of undergraduate students at the Federal University of Ceará. As a data collection instrument, a closed questionnaire consisting of two parts was used: the first part related to socioeconomic factors or questions from the researcher and the second part being formed by the academic motivation scale taken from the work of Guimarães and Bzuneck (2008) with 29 sentences grouped on a Likert scale from 1 to 4 points. As a focus, the research was applied at the Science Center Academic Unit. The electronic survey form was sent to the Management of the Science Center, and the survey was then sent to the news forum of the Integrated Academic Activities Management System (SIGAA). The working population is made up of 3053 active students, distributed among the 15 courses offered by the Science Center. It presented feedback obtained from 196 respondents, representing 6.41% of the research universe, thus considering the sample size. The estimation error of this research was in the order of 6.6 pp (percentage points). The extrinsic motivation- integrated regulation factor (average 3.38) was considered the critical motivational factor for students to remain at the university. In the general context, students do not appear unmotivated, with the average value found being 1.44. In relation to intrinsic motivation, the average value found corresponds to 2.74. Considering the different undergraduate courses evaluated, only the identified extrinsic motivation-regulation factor showed a statistically significant difference, with a significance level of 5% (p-value = 0.022) in the multiple comparison. In relation to the semester attended, it was observed that the longer the time at the institution, the greater the demotivation and students in the standard time are more intrinsically motivated. The use of exploratory factor analysis indicated, from the 29 variables studied, the emergence of seven factors that explain 61.64% of the total data variability. The Cronbach's alpha value revealed adequate internal consistency, with a value of 0.730, referring to the 29 items of the scale.